MEASUREMENT OF THE NONSENSE WORD FLUENCY: BAYESIAN APPROACH TO A ITEM RESPONSE MODEL WITH SPEEDEDNESS - BAZÁN, Jorge Luis; VALDIVIESO, Luis; BRANCO, Márcia D'Elia (Brazilian Journal of Biometrics, 2017)
Speededness refers to the situation where the time limit on a standardized test does not allow substantial number of examinees to fully consider all items in a test, thus estimation using a common three-parameter logistic item response model (3PL) can lead to contaminated estimates of the parameters in the model. This work proposes a simple Bayesian model to estimate both, personal and item parameters, from a test data with evidence of Speededness. The model is strongly related with a model proposed by Goegebeur et al. (2008) but, contrary to this, a dependence structure in the personal parameters is not initially assumed. We conduct a case study to analyze a data set of Nonsense Word Fluency in Peruvian students, which presents high evidence of Speededness. Comparing the results on this data set of the 3PL and the proposed model we found, as expected, that some difficulty and discrimination parameters are overestimated under the 3PL. Similar measures on the examinees abilities are discovered and new personal parameters: tolerance and propensity toward speededness are obtained considering the proposed model. Finally, future studies are suggested.